Ameliorative effects of apigenin on a rat model of endometriosis - Hekimoğlu, Gulam; Koç, Sümeyye; Daştan, Ali İmran and Şevgin, Kübra and Tekayev, Muhammetnur and Güler, Eray Metin and Sayir, Neslihan and Canbaz, Halime Tuba and Hacımustafaoğlu, Fatih and Pence, Halime Hanim and Sapmaz, Tansel and Kale, Ebru (The European Research Journal, 2023)
Objectives: Apigenin and parthenolide as natural products have potent antioxidant and anti-inflammatory outcomes that could make them a perfect option for endometriosis therapy. This study aimed to determine the effects of apigenin and parthenolide on created endometrial implants in a rat model of endometriosis. Methods: Thirty-nine mature, female Sprague-Dawley rats were assigned randomly to six experimental groups four weeks after endometriosis induction. Group 1 (n = 5): Control (CTRL) that opened and closed the abdomen; Group 2 (n = 6): Peritoneal and ovarian endometriosis (POE) + drug-free; Group 3 (n = 7): POE+ Apigenin (APG) (50 mg/kg); Group 4 (n = 7): POE+ Parthenolide (PTL) (10 mg/kg); Group 5 (n = 7): POE+ Apigenin (APG) (50 mg/kg) + Parthenolide (PTL) (10 mg/kg); Group 6 (n = 7): POE+ DMSO. An endometriosis model was created, and histopathological analysis and biochemical evaluation were performed. Serum and peritoneal levels of pro-and-anti-inflammatory cytokine, and oxidative stress of implant tissue were measured. Results: Serum IL-37 levels decreased significantly in the APG-treated group compared to the drug-free group (p = 0.016). The peritoneum and ovary endometriosis histopathologic scores were significantly lower in APG-treated (p = 0.001) and PTL-treated (p = 0.001) groups in comparison to the drug-free group. The oxidative stress index (OSI) values were increased statistically significantly in ovary endometriosis tissue in the drug-free group, (p = 0.001). However, compared to the drug-free group, OSI values decreased statistically significantly in the APG-treated group (p = 0.003). Conclusions: The application of apigenin caused a decrease in oxidative stress and an improvement in histopathological grade. Apigenin may be a novel therapeutic agent for the treatment of endometriosis.